Prevalence and incidence of chronic wounds and related complications: a protocol for a systematic review. Issue 1 (December 2016) - Järbrink, Krister; Ni, Gao; Sönnergren, Henrik; Schmidtchen, Artur; Pang, Caroline; Bajpai, Ram; Car, Josip
Abstract Background Chronic wounds impose a significant and often underappreciated burden to the individual, the healthcare system and the society as a whole. Preliminary literature search suggests that there are at present no reliable estimates on the total prevalence of chronic wounds for different settings and categories of chronic wounds. Such information is essential for policy and planning purposes as the increasing number of elderly and the prevalence of lifestyle diseases point in the direction of an increased burden. Knowledge about the prevalence and incidence of chronic wounds in relation to population characteristics is important for informing healthcare planning and resource allocation. The objective is to present a transparent process for how to review the existing literature on the prevalence and incidence rates of chronic wounds and resulting implications. Methods/design We will search electronic bibliographic databases (MEDLINE, EMBASE, the EBM Reviews and Cochrane, Cumulative Index to Nursing and allied Health Literature (CINAHL), PsycINFO, Global Health) and reference lists of included articles. Two investigators will independently screen titles and abstracts and select studies involving adults with chronic wounds. These investigators will also independently extract data using a pre-designed data extraction form that will cover information on demographics, diagnostics including disease prevalence, medical history, hospital and community-based management and outcomes. Subgroup analysis and sensitivity analysis will be performed to address the heterogeneity across studies. Meta-analysis will also be performed if homogeneous group of studies will be found. The collective evidence will be further stratified according to the important background variables if allowed. Discussion This study will describe the available epidemiological evidence and summarise prevalence and incidence rates of chronic wounds and related complications. A better understanding of the relationship between population profile and the prevalence of chronic wounds and related complications will be helpful in the development of guidelines for patient management. Systematic review registration PROSPEROCRD42016037355